Pore-scale simulation of gas-water flow in low permeability gas reservoirs - Cao, Ting-kuan; Duan, Yong-gang; Yu, Bo-ming; Fang, Quan-tang; Wang, Rong (Journal of Central South University, 2014)
A novel method was developed to establish a realistic three dimensional (3D) network model representing pore space in low permeability sandstone. Digital core of rock sample was established by the combination of micro-CT scanning and image processing, then 3D pore-throat network model was extracted from the digital core through analyzing pore space topology, calculating pore-throat parameters and simplifying the shapes of pores and throats. The good agreements between predicted and measured porosity and absolute permeability verified the validity of this new network model. Gas-water flow mechanism was studied by using pore-scale simulations, and the influence of pore structure parameters, including coordination number, aspect ratio and shape factor, on gas-water flow, was investigated. The present simulation results show that with the increment of coordination number, gas flow ability in network improves and the effect of invading water on blocking gas flow weakens. The smaller the aspect ratio is, the stronger the anisotropy of the network is, resulting in the increase of seepage resistance. It is found that the shape factor mainly affects the end points in relative permeability curves, and for a highly irregular pore or throat with a small shape factor, the irreducible water saturation ( S wi ) and residual gas saturation ( S gr ) are relatively high.